PH sensitive coiled coils: a strategy for enhanced liposomal drug delivery. Issue 9 (15th February 2016) - Reja, Rahi M.; Khan, Mohsina; Singh, Sumeet K.; Misra, Rajkumar; Shiras, Anjali; Gopi, Hosahudya N.
Abstract : Design of pH sensitive coiled coils and their incorporation into the liposome vesicles as triggers for the controlled release of encapsulated drugs are reported. Abstract : Stimuli responsive controlled release from liposome based vesicles is a promising strategy for the site specific delivery of drugs. Herein, we report the design of pH sensitive coiled coils and their incorporation into the liposome as triggers for the controlled release of encapsulated drugs. The designed coiled coil peptides with the incorporation of environment sensitive fluorescent amino acids were found to be stable at physiological pH and unstructured while changing the pH of the environment to either acidic or basic. This pH dependent conformational switch of the coiled-coil polypeptides was exploited as triggers for the enhanced release of the encapsulated drug molecules from liposomes. The SEM, DLS and TEM analysis revealed the uniform morphology of the peptide liposome hybrid vesicles. Further, the drug encapsulated liposome internalization experiments with cancer cells revealed the enhanced release and accumulation of drugs in the acidic lysosomal compartments in comparison with liposomes without coiled coils.